How E. Vodolazkin’s Laurus Was Made - Kupka, Valery (Slavica, 2021)
In the paperan attempt has been made to define the basic principles of the composition of E. Vodolazkin's novel Laurus and their role in creating an atmosphere of timelessness and ahistoricism in the novel. The possible influence of the ancient Russian hagiographic icon on the nature of the composition is also investigated.